Morphological segmentation and reading difficulties in children with reading and writing disorders - Liliana Gomes; Rui Ramos; Rosa Lídia Coimbra (Calidoscópio, 2016)
This study aims to verify the existence of a correlation between morphological awareness and reading and writing performance (more precisely, in the reading component) in children with and without reading and witting difficulties or disorders. To fulfill this objective, a sample of European Portuguese-speaking children was tested with two assessment instruments: the “Reading Age Test” and a Morphological Awareness Test specifically created for this purpose. The experimental group (EG) includes children who have been diagnosed with reading and writing difficulties or disorders; the control group (CG) has not. After analyzing the data, it was concluded that there is a statistically significant difference between the groups of children in the study, since the CG reveals a better performance than the EG in both tests applied. The results also show a statistically significant correlation between the children’s reading performance and their morphological awareness. The correlation appears to be considerably stronger in the EG than in the CG. Thus, we concluded that stimulation of morphological awareness can effectively facilitate and help children’s reading skill development, especially in children having difficulties in these areas. Keywords: metalanguage, morphological awareness, reading and writing disorders.